(untitled) (Boston, 2009)
Offers the articles - from some of the most respected magazines, newspapers, and journals - that are authored by scholars, researchers, and commentators writing for a general audience. This title includes: a general introduction; an annotated table of contents; a topic guide; and, an annotated listing of selected World Wide Web sites
Keywords: Environmental sciences,Khoa học môi trường